2011
DOI: 10.1097/igc.0b013e3182009eea
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of p16ink4a Immunoexpression/Immunostaining and Human Papillomavirus DNA Test in Cervical Liquid-Based Cytological Samples

Abstract: The findings suggest that p16INK4a immunostaining can improve the accuracy of cytological examination and HPV DNA test and may be particularly useful in the triage of low-grade lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…Twelve studies 2325;2833;3638 used clone E6H4 as a primary antibody for p16 INK4a , other primary antibodies used were Clone 6H12 27 , Clone JC8 34 and 16P04 35 . Positivity criteria of p16 INK4a immunostaining differed between the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies 2325;2833;3638 used clone E6H4 as a primary antibody for p16 INK4a , other primary antibodies used were Clone 6H12 27 , Clone JC8 34 and 16P04 35 . Positivity criteria of p16 INK4a immunostaining differed between the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Positivity criteria of p16 INK4a immunostaining differed between the studies. Five studies 25;30;33;37;38 made use of the nuclear scoring proposed by Wentzensen and Bergeron 39 . This scoring system takes into account nuclear staining and nuclear abnormalities (increased size, granular/hyperchromatic chromatin, irregular shape or variable morphology from cell to cell).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sensitivity ranging from 75%[26] to 95%[14] and specificity ranging from 23.3%[14] to 92%[27] has been previously reported. Moreover, p16 showed 46.2% positivity for LSIL lesions and 100% positivity for HSIL lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [9] demonstrated that p16 INK4A ICC can significantly improve SP and PPV of colposcopy in the management of women with ASC-US cytology. Although studies vary in their methodological approach, and conclusions are usually drawn from cases pre-selected for colposcopy, they clearly demonstrate (1) a strong correlation between positive p16 INK4A cytological staining and the severity of the histological lesion [10,11,12]; (2) the potential to increase the accuracy of cytological examination [12,13,14,15,16,17], and (3) the potential for efficient triage of ASC-US [9,18,19,20], ASC-H [6,21], and LSIL [18,19,20] cases.…”
Section: What Are the Main Goals For Immunomarkers?mentioning
confidence: 99%